Reduced neutralizing antibody titer against genotype I virus in swine immunized with a live-attenuated genotype III Japanese encephalitis virus vaccine - Fan, Yi-Chin; Chen, Jo-Mei; Chen, Yi-Ying; Lin, Jen-Wei; Chiou, Shyan-Song (Veterinary microbiology, 2013)
A shift in prevalence from Japanese encephalitis virus (JEV) genotype III (GIII) to GI virus has been observed in several Asian countries. Genotype I virus was first detected in Taiwan in 2008, and became the dominant JEV island-wide within a year. We conducted a serosurvey using swine serum specimens from multiple counties in Taiwan following the transmission season in 2009 and results showed 67–100% of JEV seropositive swine showed evidence of GI virus infection. The envelope (E) protein is a structural protein that elicits protective neutralizing antibodies (Nt Ab). The GIII at222 (a live-attenuated swine vaccine) virus E protein differs at eight amino acid residues (E-123, E-129, E-138, E-176, E-209, E-222, E-327 and E-366) from that of the GI TC2009-1 strain (isolated in Taiwan in 2009). Twenty piglets were vaccinated with two doses of at222 vaccine, and serum specimens were collected to evaluate the strain-specific Nt Ab titer against GIII at222, GIII CJN, and GI TC2009-1 viruses. Seropositivity rates (Nt Ab titer≥1:10) and geometric mean titers (GMT) were similar against at222 and CJN viruses. However, sera from swine vaccinated with at222 were least potently neutralizing against GI TC2009-1 virus. The estimated protective threshold against GI virus was observed only when the PRNT50 against at222 virus was ≥1:320. Thus, our current study indicates that the live-attenuated at222 swine vaccine can be partially protective against GI virus, and suggests that the efficacy of GIII swine vaccines currently used may require a comprehensive reevaluation in the field.